Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.15406/aovs.2017.07.00240
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Utilization of Eye Care Services in the Upper East Region, Ghana

Abstract: The aim of the study was to determine the barriers to utilization of eye care services in the Upper East region of Ghana. A descriptive cross-sectional study in which 350 participants were randomly sampled from 8 district capitals and one settlement. These locations were selected for the study because an eye care facility was located in each of them. Interview of participants was conducted using structured questionnaires. Majority (53.71%) of the participants were females. Forty percent (40.00%) of the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
(12 reference statements)
1
14
0
Order By: Relevance
“…In the present study of 338 participants, 141 (41.7%) did not have their eye examination up to date, taking into account the recommendations of the American Optometric Association and American Academy of Ophthalmology (periodicity of at least 2 years for patients without risk factors and aged between 18–64 years and annually for patients aged ≥65 years or with risk factors) [ 28 , 30 ]. In a study carried out in Ghana [ 20 ], similar results were found, although 3 years were used as a parameter: 40.0% of the participants did not have their eye examination up to date at the time of the research. In studies carried out in Southwest Nigeria [ 19 ] and Ethiopia [ 6 ], the percentages were higher (81% and 76.2%, respectively) compared to our study.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the present study of 338 participants, 141 (41.7%) did not have their eye examination up to date, taking into account the recommendations of the American Optometric Association and American Academy of Ophthalmology (periodicity of at least 2 years for patients without risk factors and aged between 18–64 years and annually for patients aged ≥65 years or with risk factors) [ 28 , 30 ]. In a study carried out in Ghana [ 20 ], similar results were found, although 3 years were used as a parameter: 40.0% of the participants did not have their eye examination up to date at the time of the research. In studies carried out in Southwest Nigeria [ 19 ] and Ethiopia [ 6 ], the percentages were higher (81% and 76.2%, respectively) compared to our study.…”
Section: Discussionsupporting
confidence: 59%
“…Prior to the interview, a rapid review in PubMed and Google Scholar about the possible barriers to the access or use of eye health services was performed; the keywords defined as barriers to accessing eye health services were extracted, both for the eye examination as well as treatment (optical, drug, or surgical), which served as a guide for the interviews. The most common barriers found in the literature were cost, transportation, lack of information or education in eye care, fear of treatment, traditional treatment, trust, lack of time, not being aware of the problem, need for escort, and unhappy with medical services [ 6 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Nevertheless, a qualitative study with data saturation was carried out to collect the existence of more barriers.…”
Section: Methodsmentioning
confidence: 99%
“…With the uneven distribution of workforce, the populace of regions with deficient workforce would have to travel longer distances for eye care. Also, with just few eye care personnel serving a large proportion of the populace, the patient load on these personnel would be extremely high, which would result in longer waiting time at the facilities, preventing many people from accessing essential eye care [51].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO have also developed an eye care assessment tool 158 (ECSAT) comprising a detailed checklist based on the WHO health system approach framework, 159 which organises health systems around six fundamental components or “building blocks”: leadership and governance, financing, the health workforce, service delivery, access to vital medicines and health information systems. The ECSAT tool gives an overview of the primary gaps, requirements, and information requiring further research as well as advised measures to address these issues within a country 166 . Whereas our framework allows for the evaluation of existing services as well as the creation of new sustainable eye care services through the incorporation of research priorities (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…The ECSAT tool gives an overview of the primary gaps, requirements, and information requiring further research as well as advised measures to address these issues within a country. 166 Whereas our framework allows for the evaluation of existing services as well as the creation of new sustainable eye care services through the incorporation of research priorities (Figure 9).…”
Section: Implications For Clinical Practice and Eye Care Policy Inter...mentioning
confidence: 99%